Thrombosis of Digital Arteries Associated with Tamoxifen Use: Case Report - Hutchison, Richard L.; Rayan, Ghazi M. (Journal of Reconstructive Microsurgery, 2012)
Arterial thrombosis in the upper extremity occurs often at the wrist. We report a unique case of thrombosis that involved multiple digital arteries, without radial or ulnar artery involvement, which developed only after using tamoxifen despite chronic occupational blunt percussive hand use. Revascularization was achieved after thrombectomy. Multiple digital arterial thromboses may complicate the use of tamoxifen.
Keywords: catheter; digital artery thrombosis; digital ischemia; tamoxifen; thrombectomy